Pseudomonas aeruginosa inhibits quorum-sensing mechanisms of soft rot pathogen Lelliottia amnigena RCE to regulate its virulence factors and biofilm formation - Kapadia, Chintan; Kachhdia, Rinkal; Singh, Susheel; Gandhi, Kelvin; Poczai, Peter; Alfarraj, Saleh; Ansari, Mohammad Javed; Gafur, Abdul; Sayyed, R. Z. (Frontiers in Microbiology, 2022)
The quorum sensing (QS) cascade is responsible for the colonization and phenotypic behavior of the pathogenic organism and it is regulated by the diverse signal molecules. The disruption of the quorum-sensing system is an effective strategy to overcome the possibility of antibiotic resistance development in pathogens. The quorum quenching does not kill the microbes rather it hinders the expression of pathogenic traits. In the present experiment, Pseudomonas aeruginosa RKC1 was used to extract the metabolites responsible for quorum sensing inhibition in soft rot pathogen, L.amnigena RCE. During the initial screening, P. aeruginosa RKC1 was found to be most promising and inhibits violacein of Chromobacterium violaceum MTCC 2656 and inhibits pyocyanin, swarming-swimming motility of P. aeruginosa MTCC 2297. The characterization of metabolites responsible for quorum sensing inhibition by GC-MS is very scarce in scientific literature. The ethyl acetate extract of P. aeruginosa RKC1 inhibits biofilm formation of L. amnigena RCE while it inhibits growth at higher concentrations. The GC-MS analysis suggested that Cyclic dipeptides (CDPs) like Cyclo (L-prolyl-L-valine), Cyclo (Pro-Leu), Cyclo(D-phenylalanyl-L-prolyl) were predominantly found in the ethyl acetate extract of the P. aeruginosa RKC1. This diketopiperazine (DKPs) exhibited quorum sensing inhibition against the pathogen in liquid media during the active growth phase and regulate diverse metabolites of the pathogen. Moreover, the metabolites data from the clear zone around wells showed a higher concentration of DKSs. So far, very few reports indicate the role of DKPs or CDPs to inhibit the quorum sensing systems in plant pathogenic bacteria and this is one of such report that exploits metabolites of P. aeruginosa RKC1. These investigations provided further evidence to use quorum sensing inhibitor metabolites, diketopiperazine, to suppress the pathogenesis of microbes and thus develop innovative strategies to overcome antibiotic resistance.